2017
DOI: 10.1080/03007995.2017.1297700
|View full text |Cite
|
Sign up to set email alerts
|

Safety profiles of non-small cell lung cancer patients treated with pemetrexed plus carboplatin: a real-world retrospective, observational, cohort study

Abstract: Results from this real-world analysis add to existing evidence from randomized clinical trials about PCb safety profiles in the overall NSCLC population and in elderly patients. These results may guide physicians when making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…All tissues were stored at -80°C and were confirmed as NSCLC. Inclusion criteria were as follows: (1) Patients diagnosed with NSCLC according to diagnostic standards [19] by cytologist or pathologist and were unable or unwilling to undergo surgery; (2) The age range was 18 - 75 years, the Karnofsky score was greater than 70, and the expected survival time was more than 6 months using an objective measurable lesion index. The routine blood parameters, liver, kidney functions and electrocardiographs (ECG) were normal prior to receiving treatment.…”
Section: Methodsmentioning
confidence: 99%
“…All tissues were stored at -80°C and were confirmed as NSCLC. Inclusion criteria were as follows: (1) Patients diagnosed with NSCLC according to diagnostic standards [19] by cytologist or pathologist and were unable or unwilling to undergo surgery; (2) The age range was 18 - 75 years, the Karnofsky score was greater than 70, and the expected survival time was more than 6 months using an objective measurable lesion index. The routine blood parameters, liver, kidney functions and electrocardiographs (ECG) were normal prior to receiving treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, chemotherapy is still indispensable (4)(5)(6). Some randomized controlled trials and real-world studies abroad demonstrated that pemetrexed-cisplatin induction and pemetrexed maintenance therapy is an effective and well-tolerated regimen in stage IIIB-IV patients with non-squamous NSCLC (7)(8)(9)(10)(11)(12)(13)(14), but there is still a lack of large sample size evidence to report the survival benefit of pemetrexed as the initial chemotherapy in Chinese patients with advanced lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%